The Analisa Pengaruh Kepuasan Pengguna Website Talipodo Golden Theatre Menggunakan Metode Webqual 4.0 - Reka Ainul Khasanah; Sucipto; Arie Nugroho (Bulletin of Information Technology (BIT), 2025)
This study aims to assess the quality of the Golden Theatre website based on user satisfaction using the WebQual 4.0 method. The research focuses on three main dimensions: usability, information quality, and service interaction quality. A quantitative descriptive approach was employed through a survey of 100 active users of the Golden Theatre website. Data were analyzed using Prais-Winsten regression and classical assumption tests, processed with Python programming language. The results indicate that among the three variables, only information quality has a significant influence on user satisfaction. Meanwhile, usability and service interaction quality do not have a significant partial effect. Simultaneously, the three variables have a significant impact on user satisfaction. The WebQual Index (WQI) score of 57.19% suggests that the website’s overall quality is moderate but still falls short of user expectations. Therefore, it is recommended that the Golden Theatre website management enhance the quality of information provided, in order to improve service quality and overall user satisfaction.